Lancet Commission on Global Surgery - A Public Health Initiative - Kurlberg, Göran (Journal of Institute of Medicine Nepal, 2020)
With the advent of the epidemiological transition, the incidence of non-communicable diseases (NCDs) presenting as cardiovascular disease, diabetes, hypertension, malignancies and injuries make up the major part of the Global Burden of Disease. Many of these conditions will require surgery and in 2015, the Lancet Commission on Global Surgery was launched. The Commission´s key findings reveal that human and economic consequences of unmet surgical needs in low and middle-income countries (LMIC) are substantial and for many years have gone unrecognised.